Spleen Size and Function in Sherpa Living High, Sherpa Living Low and Nepalese Lowlanders - Holmström, Pontus; Mulder, Eric; Starfelt, Victor; Lodin-Sundström, Angelica; Schagatay, Erika (Frontiers in Physiology, 2020)
High altitude (HA) natives have evolved beneficial responses leading to superior work capacity at HA compared to native lowlanders. Our aim was to study two potentially protective responses against hypoxia, namely; the cardiovascular diving response and the hemoglobin concentration (Hb) elevating spleen contraction in Sherpa highlanders, compared to lowlanders. Male participants were recruited from three groups: 1) 21 Sherpa living at HA (SH); 2) seven Sherpa living at low altitude (SL); 3) ten native Nepalese lowlanders (NL). They performed three apneas spaced by two minutes rest at low altitude (1370m). Their peripheral oxygen saturation (SpO2), heart rate (HR) and spleen volume were measured before, during and following the apnea protocol. Spleen volume at rest was 198±56mL in SH and 159±35mL in SL (p=0.047). The spleen was larger in Sherpa groups compared to the 129±22mL in NL (p<0.001 compared to SH; p=0.046 compared to SL). HR was lower in Sherpa groups compared to NL both during rest (SL: p<0.001; SH: p=0.003) and during maximal apneas (SL: p<0.001; SH: p=0.06). The apnea-induced HR-reduction was 8±8% in SH, 10±4% in SL (NS) and 18±6% in NL (SH: p=0.005; SL: p=0.021 compared to NL). Resting SpO2 was similar in all groups. The progressively decreasing baseline spleen size across SH, SL and NL suggests a role of the spleen at HA, and further that both genetic predisposition and environmental exposure determine human spleen size. The similar HR responses of SH and SL suggest a genetic component is responsible for the cardiovascular diving response.